Relationship between ‘Big Data’, ‘Internet of People &Thing’ and ‘Internet of Signs &Things’ - Sen, Vidhi; Mishra, Priyanka (International Journal of Engineering and Technology, 2018)
This paper will try to determine the co-relationship exist in between ‘Big Data’, the ‘Internet of People and Things’ and the ‘Internet of Signs.’ Specifically , we will find out various ways through which the ‘things’ present in the ‘Internet of Things’ makes ‘Big Data’, and the various ways through which both are combined in order to form semiotic ‘signs’. We will find out how context is important and also the various types of relations that exists in between ‘Big Data’, the ‘Internet of People & Things’, and the ‘Internet of Signs’.